Escoamento particulado com fluido não newtoniano em canal vertical e fraturado - Pereira, Felipe Barboza (2022)
In oil and gas exploration operations, the loss of fluid circulation is one of the main problems that interfere in the well drilling process. The presence of fractures, frequent in the reservoirs, added to the pressure gradients in the well, significantly accentuates the leakage of fluid into the rock formation. The addition of LCM (lost circulation materials) to the drilling fluid is an alternative corrective method used to mitigate and control the problem. In the present work, a combination of LCM with non-Newtonian fluid to fill in a fracture is experimentally analyzed. The proposed tests were performed in an experimental apparatus composed by a rectangular test section, which represents the well-formation in the presence of a discrete fracture, using measuring equipments to monitor the pressure, the flow rate and the temperature. Results show the influence of the variation in the parameters of the flow regime (Reynolds number and fluid flow rate through the fracture), of the fluid (apparent viscosity) and of the LCM (concentration and granulometry). The lost circulation was characterized by monitoring the flow rate through the fracture and the pressure gradients in the fracture and free channel throughout the LCM injection process. As a whole the usage of LCM combined with non-Newtonian fluid was effective for treating the lost circulation problem. Out of the obtained results, it was verified that the usage of a particulate material with a granulometry of 0.363 mm as LCM, with a fluid of an apparent viscosity of 10cP, was able to handle the lost circulation returning the flow rate at a 100% in the free channel after occur a fluid loss through the fracture equal to 35%.